PEMBUATAN FLASH CARD DIGITAL UNTUK PEMBELAJARAN 80% KOSA KATA AL-QUR’AN - Raden Arfan Rifqiawan (At-Taqaddum, 2016)
This study is realized in the manufacture of digital flashcards vocabulary 80% of the Qur’an. Begins with a study of journals, books, and articles on the internet about the vocabulary of the Qur’an. Then proceed with the creation of a digital database. This database is the source of 80% of the vocabulary of the Qur’an booklet which is the result of research by Dr. Abdul Aziz Abdul Raheem from India. Once the database is materialized and the result is save as in the format tab-separated.txt with UFT-8 encoding, then followed with a database that has finished importing into Anymemo android application. The final step is to test whether a digital flashcard can run either smartphone or tablet and share the application to the public.